Coworker Networks from Student Jobs: A Flying Start at Labor Market Entry? - Gökay Demir; Friederike Hertweck; Malte Sandner; Ipek Yükselen (Institute of Labor Economics (IZA), 2024)
This paper analyzes the impact of college students' coworker networks formed during student jobs on their labor market outcomes after graduation. For our analysis, we use novel data that links students' administrative university records with their pre- and post-graduation employment registry data and their coworker networks. Our empirical strategy exploits variation in the timing and duration of student jobs, controlling for a variety of individual and network characteristics, as well as firm-by-occupation fixed effects, eliminating potential selection bias arising from non-random entry into student jobs and networks. The results show that students who work alongside higher-earning coworkers during their student jobs earn higher wages in their first post-graduation employment. Two key mechanisms appear to drive this effect: (1) sorting into higher-paying firms after graduation, facilitated by coworker referrals, and (2) enhanced field-specific human capital through exposure to skilled colleagues. However, the initial wage advantage from higher-earning coworker networks diminishes over time as students with worse networks catch up. Our findings contribute to the understanding of how early career networks shape labor market outcomes and facilitate a smoother transition from higher education to graduate employment.
Keywords: I23; J24; J31; 330; labor market entry; student jobs; coworker networks; wages